Analisa Minimalisasi Biaya Terapi PPI (Proton Pump Inhibitor) pada Pasien Rawat Inap Bedah di RSUD Dr. Zainoel Abidin Menggunakan Form Restriksi - Suherman; Ika Wahyuningrum; Yunita Suffiana (Journal of Medical Science, 2021)
Based on data on the use of PPI class drugs for the last 6 months, at December 2020-May 2021 at RSUDZA, the PPI drug class is among the drugs that are widely used every year, it is also prescribed for use other than cases of gastric acid secretion disorders and hematemesis melena, it can have an impact on optimization of drug spending costs so that if the hospital cannot control the drug spending budget and it can have an impact on the hospital's cash flow. This study aims to analyze the cost minimization of PPI (proton pump inhibitor) therapy in surgical inpatients at RSUD dr. Zainoel Abidin uses a restriction form. This study is an analytical intervention study with a prospective method and based on inclusion criteria by looking at the medical records of inpatients Neurosurgery and Orthopedics in Raudhah 3,4, and 5 by filling out the research tool used is the request sheet for restriction drugs of the PPI (Proton Pump Inhibitor) class., data collection was carried out from July-October 2021 using purposive sampling. The cost analysis used in this study is CMA (Cost Minimization Analysis), Chi-Square test to see the effect between two groups of variables, Kolmogorov Smirnove normality test to analyze data normality, and Mann Whitney to see the mean difference between groups pretest-posttest. The results showed that the use of PPI therapy in this study mostly used Omeprazole 40 mg iv therapy is 98%. There was an effect of giving a PPI restriction form to decrease the frequency of using Omeprazole 40 mg iv to every 24 hours for prophylactic statistically (p<0.000). Analysis of the cost of CMA in neurosurgery patients found that there was no decrease in the cost of Omeprazole 40 mg iv therapy in the restriction form treatment group, analysis of the cost of CMA in orthopedic surgery patients found a decrease in the cost of Omeprazole 40 mg iv therapy in the treatment group using the restriction form. Factors that influence the cost analysis in this study are length of stay, types of other drug items obtained during treatment, type of surgery, and duration of use of PPI class therapy.